Therapeutic Endoscopy in Postoperative Pouch Complications - Chandan, Saurabh; Shen, Bo; Kochhar, Gursimran S. (Clinics in Colon and Rectal Surgery, 2022)
Ileal pouch-anal anastomosis (IPAA) or “J”-pouch as it is commonly referred to, is the treatment of choice in patients with medically refractory ulcerative colitis. IPAA can have infectious, inflammatory, and mechanical complications. Currently, there are no Food and Drug Administration-approved medical therapies for these complications. Surgery that may be eventually required can have significant morbidities due to the complexity of IPAA. Endoscopy is fast emerging as a leading modality of treatment for some of these pouch complications. Endoscopy in adjunct with medical treatment can help manage the majority of pouch-related disorders and improve the outcome.
Keywords: ileal pouch-anal anastomosis; Crohn's disease; ulcerative colitis